Effect of Plasma, RF, and RIE Treatments on Properties of Double-Sided High Voltage Solar Cells with Vertically Aligned p-n Junctions - Mykola O. Semenenko; Mykhailo G. Dusheiko; Sergiy V. Mamykin; Valeriy O. Ganus; Mykhailo V. Kirichenko; Roman V. Zaitsev; Mykola M. Kharchenko; N. I. Klyui (International Journal of Photoenergy)
Si-based solar cells with vertically aligned p-n junctions operating at high voltage were designed and fabricated. The plasma treatments and antireflection coating deposition on the working surfaces of both single- and multijunction cells were made using the special holders. It was shown that additional treatment of solar cells in argon plasma prior to hydrogen plasma treatment and deposition of diamond-like carbon antireflection films led to the improvement of the cell efficiency by up to 60%. Radio frequency waves support plasma generation and improve photoelectric conversion mainly due to reduction of internal stresses at the interfaces. Application of reactive ion etching technique removes the broken layer, reduces elastic strain in the wafer, decreases recombination of charge carriers in the bulk, and provides cell efficiency increase by up to ten times.